Occurrence of Transferable Integrons and sul and dfr Genes Among Sulfonamide-and/or Trimethoprim-Resistant Bacteria Isolated From Chilean Salmonid Farms - Domínguez, Mariana; Miranda, Claudio D.; Fuentes, Oliver; de la Fuente, Mery; Godoy, Félix A.; Bello-Toledo, Helia; González-Rocha, Gerardo (Frontiers in Microbiology, 2019)
Salmon farming industry in Chile currently uses a significant quantity of antimicrobialsto control bacterial pathologies. The main aims of this study were to investigate the presence of transferable sulfonamide- and trimethoprim-resistance genes, sul and dfr, and their association with integrons among resistant Gram-negative strains recovered from Chilean salmon farming. For this purpose, 91 strains recovered from various sources of 7 Chilean salmonid farms were studied for thepresence of these genesusing PCR, with specific primers. 28 strains (30.8%) were found to carry at least one type of sul gene, mainly associated with a class 1 integron (17 strains), and identified by 16S rRNA gene sequencing as mainly belonging to the Pseudomonas genus (21 strains). Of these, 22 strains carried the sul1 gene, 3 strains carried the sul2 gene and 3 strains carried both the sul1 and sul2 genes. Among these, 19 strains also carried the class 1 integron-integrase gene intI1, 1 strain also carried the dfrA1 gene, 6 strains carried the dfrA12 gene, 2 strains carried the dfrA14 gene and 2 strains simultaneously carried the dfrA1 and dfrA12 genes or the dfrA12 and dfrA14 genes. Otherwise, the sul3 and intI2 genes were not found, whereas the intI1 gene was also detected in 2 strains not carrying any sul or dfr genes. In addition, the capacity to transfer these resistance determinants by conjugation was evaluated in 6 selected strains.Sulfonamide resistance was successfully transferred by all assayed strains, mainly mediated by a 10 kb plasmid, with a frequency of transfer of 5.0×10-4 to 8.4×10-3 transconjugant per recipient cell, and exhibiting a co-transference of resistance to florfenicol and oxytetracycline, currently the most used antibiotic in the Chilean salmon industry, suggestingan antibacterial co-selection phenomenon.Donor strains identified as Citrobacter gillenii and Kluyvera intermedia transferred simultaneously sul1 and sul2 genes suggesting that they are located on the same plasmid. This is the first report of the characterization and transferability of integrons as well as sul and dfr genes among bacteria associated with Chilean salmon farms, indicating a relevant role of this environment as a reservoir of these genes.